The Effect of Parents Social Economic Support on the Motivation of Learning the Accounting Economy of Public SMAN 17 Makassar - Farial B Karim; Muhammad Azis; Sahade Sahade (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the effect of parents' social economic support on the motivation to study the accounting economy of public SMA Negeri 17 Makassar. The variables in this study are the parents' social economic support as the independent variable and the motivation of learning the accounting economy as the dependent variable. The population in this study is the entire IPS of SMA Negeri 17 Makassar. The sampling technique used the proportionate stratified random sampling technique, samples from the population were selected randomly and proportionally with a sample of 57 students. Data collection techniques used are questionnaires and documentation. The data analysis technique used is descriptive analysis of percentages , instrument testing, and hypothesis testing. Based on the data analysis that has been carried out, the result of a descriptive analysis of social economic support of parents is 91.2% which is classified as excellent and motivation for learning an accounting economy is 97.1% which is classified as excellent. The result of simple linear regression analysis obtained by the equation model Y = 31.510 + 0.636X, which means that each addition of 1 unit of parents social economic support, the motivation of learning the accounting economy increases 0.636. From the result of the analysis of the coefficient of determination (r 2 ), the value of r 2 = 0.431 this means that the influence of a parent's social economy on the motivation of learning the accounting economy of 43.1% and the remaining 56 .9% is influenced by other factors. Meanwhile, based on the results of the Pearson product moment correlation analysis, the correlation coefficient is 0.656 and falls into a good category which means that there is a good relationship between the social economic support of parents and the motivation of learning the accounting economy of SMA Negeri 17 Makasar. Meanwhile, the result of the t-test analysis obtained a significant value of 0.000 <0.05, which means that parents' social economic support has a positive and significant effect on the motivation for studying an accounting economy, this hypothesis is accepted.